Relationships between Epistemological Beliefs and Conceptual Understanding of Evolution by Natural Selection - Andreani Baytelman; Theonitsa Loizou; Salomi Hadjiconstantinou (Center for Educational Policy Studies Journal, 2023)
This study researches relationships between 12th-grade students’ epistemological beliefs towards science and their conceptual understanding of evolution by natural selection. Forty-two 12th-grade students in a suburban high school in Cyprus, who participated in a biology course, completed measures of their: (a) epistemological beliefs towards science before the intervention of being taught evolution n (b) conceptual understanding of evolution by natural selection after evolution intervention, (c) epistemological beliefs towards science after evolution intervention. Based on previous research, we hypothesised there would be a significant relationship between students’ epistemological beliefs and their conceptual understanding of evolution by natural selection after the evolution intervention. We also hypothesised that inquiry-based intervention on evolution by natural selection would foster students’ epistemological beliefs. Our results indicate that participants’ initial epistemological beliefs predict very modestly and statistically non-significant learning achievements on conceptual understanding of evolution by natural selection. However, our results show a significant improvement in participants’ epistemological beliefs after engagement in an inquiry-based intervention on evolution by natural selection. The educational significance of this and its implications are discussed.